Using a Two-Sample Mendelian Randomization Method in Assessing the Causal Relationships Between Human Blood Metabolites and Heart Failure - Wang, Zixian; Chen, Shiyu; Zhu, Qian; Wu, Yonglin; Xu, Guifeng; Guo, Gongjie; Lai, Weihua; Chen, Jiyan; Zhong, Shilong (Frontiers in Cardiovascular Medicine, 2021)
ABSTRACT BACKGROUND Heart failure (HF) is the main cause of morbidity and mortality worldwide, and metabolic dysfunction is an important factor related to HF pathogenesis and development. However, the causal effect of blood metabolites on HF remains unclear. OBJECTIVES Our chief aim is to investigate the causal relationships between human blood metabolites and HF risk. METHODS We used an unbiased two-sample Mendelian randomization (MR) approach to assess the causal relationships between 486 human blood metabolites and HF risk. Exposure information was obtained from Sample 1, which is the largest metabolome-based genome-wide association study (mGWAS) data containing 7,824 Europeans. Outcome information was obtained from Sample 2, which is based on the results of a large-scale GWAS meta-analysis of HF and contains 47,309 cases and 930,014 controls of Europeans. The inverse variance weighted (IVW) model was used as the primary two-sample MR analysis method and followed the sensitivity analyses, including heterogeneity test, horizontal pleiotropy test and leave-one-out analysis. RESULTS We observed that 11 known metabolites were potentially related to the risk of HF after using the IVW method (P < 0.05). After adding another four MR models and performing sensitivity analyses, we found a 1-SD increase in the xenobiotics 4-vinylphenol sulfate was associated with approximately 22% higher risk of HF (OR [95%CI], 1.22 [1.07-1.38]). CONCLUSIONS We revealed that the 4-vinylphenol sulfate may nominal causal increase the risk of HF by 22% after using a two-sample MR approach. Our findings may provide novel insights into the pathogenesis underlying HF and novel strategies for HF prevention.